(3OjhGf Uaj GdOjf GdMdjs - (3GdSfHSj GdWGFj GdMdj, Uaj GdOjf, YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe, (B750 (3g`s
(3ChdgG (B:s
(3ajQhRL GdUHM Ce jGbhJg GdTab (B*** (3HOJ agjLJ GdhQb ef CQb , Ce VGQe GdUHM deG dGM eNJVHG (B*** (3ceG HOG GdSja eMeQG ef GdYdbs
(3BNQgG (B:s
(3dbO QaYJe HESOGA GdLejd dce (B*** (3PcQG EPG bHV Gddg GdCfGe Hbi , dG RGd jgej Ydi GdhaG fCjdce (B*** (3HhGHd ef SMGH GdLhGO efOabs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 18s
(3eYLe GdeDdajf(B: 2 / 160s
(3cTa GdXfhf(B: 2 / 797s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs